2018
DOI: 10.1021/acsami.8b06671
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Performance of TiCaPCON Films Incorporated with Ag, Pt, and Zn: Bactericidal Ions Versus Surface Microgalvanic Interactions

Abstract: It is very important to prevent bacterial colonization at the early postoperative stages. There are four major strategies and their corresponding types of antibacterial surfaces specifically designed to fight infection: bactericide release, anti-adhesion, pH-sensitive, and contact-killing. Herein, we aimed at determining the antibacterial efficiency of different types of bactericidal ions and revealing the possible contribution of surface microgalvanic effects arising from a potential difference on heterogeneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…The spectra were fitted using CasaXPS software after subtracting Shirley-type background. The binding energy (BE) values for all carbon, titanium, and nitrogen environments were taken from the available literature [23,[25][26][27]. The BE scale was calibrated by shifting CH x component to 285.0 eV.…”
Section: Materials Characterizationmentioning
confidence: 99%
“…The spectra were fitted using CasaXPS software after subtracting Shirley-type background. The binding energy (BE) values for all carbon, titanium, and nitrogen environments were taken from the available literature [23,[25][26][27]. The BE scale was calibrated by shifting CH x component to 285.0 eV.…”
Section: Materials Characterizationmentioning
confidence: 99%
“…The addition of copper into mesoporous bioactive glass scaffolds or Cu-Zn nanoparticles into chitosan/nano-hydroxyapatite scaffolds conferred antibacterial and osteoproliferative properties on the scaffolds [10,33], Jin et al revealed that Zn-implanted titanium had antibacterial effects on E. coli and stimulated the spreading activity, adhesion, ALP activity and extracellular matrix mineralization of rat mesenchymal stem cells [14]. Znmodified TiCaPCON films showed a significantly antibacterial effect against E. coli and S. aureus strains and good osteoconductive characteristics [13]. In our present study, the PLGA/Cu(I)@ZIF-8 scaffolds provided a continuous release of Cu(I) ions even after 24 days of incubation in SBF solution; while ZIF-8 nanoparticles themselves possessed antibacterial activity [15].…”
Section: Antibacterial Assessment Of Plga/cu(i)@zif-8 Scaffolds In VImentioning
confidence: 99%
“…Based on the antibacterial and bone-forming activity of copper, copper coated Ti6Ai4V nails have also been studied to treat implant-related infections [8]. Zinc ions are also known to contribute to antibacterial and osteoconductive effects [9][10][11][12][13][14]. For example, zinc (Zn)-doped mesoporous hydroxyapatite microspheres/ collagen (Zn-MHMs/Coll) scaffolds enhanced osteogenic differentiation of rat bone marrow-derived mesenchymal stem cells and accelerated the formation and healing of bone compared to pure Coll scaffolds or MHMs/ Coll scaffolds [9].…”
mentioning
confidence: 99%
“…Silver ions have shown high bactericidal activity by inhibiting DNA and protein synthesis 21 . The antibacterial property of silver ions has already been utilized in topical antiseptics and in coatings for orthopedic implants 22 24 . The silver leads to changes in protein structure and inactivation of many enzymes 25 .…”
Section: Introductionmentioning
confidence: 99%
“…2 These authors contributed equally: Virendra Kumar and Adity Chopra. * email: vkbhalla@imtech.res.in and in coatings for orthopedic implants [22][23][24] . The silver leads to changes in protein structure and inactivation of many enzymes 25 .…”
mentioning
confidence: 99%